2022
DOI: 10.1002/advs.202204881
|View full text |Cite
|
Sign up to set email alerts
|

Arthritic Microenvironment Actuated Nanomotors for Active Rheumatoid Arthritis Therapy

Abstract: Increasing O 2 demand and excessive ROS production are the main features of arthritic microenvironment in rheumatoid arthritis (RA) joints and further play pivotal roles in inflammation exacerbation. In this work, a system of in situ regulation of arthritic microenvironment based on nanomotor strategy is proposed for active RA therapy. The synthesized MnO 2 -motors enable catalytic regulation of RA microenvironment by consuming the overproduced H 2 O 2 and generating O 2 synergistically. The generated O 2 unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Meanwhile, in vitro experiments confirmed that the nanozyme could induce the transformation of macrophages from the M1 subtype to the M2 subtype. Xu et al 209 reported a H 2 O 2 -driven MnO 2 nanozyme based on the arthritis microenvironment, which could alleviate hypoxia and remove ROS. Improvement of the local microenvironment inhibits phenotypic polarization of the M1-type macrophages, and thus reduces the inflammatory response (Figure 12A).…”
Section: Treatment Of Motor Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, in vitro experiments confirmed that the nanozyme could induce the transformation of macrophages from the M1 subtype to the M2 subtype. Xu et al 209 reported a H 2 O 2 -driven MnO 2 nanozyme based on the arthritis microenvironment, which could alleviate hypoxia and remove ROS. Improvement of the local microenvironment inhibits phenotypic polarization of the M1-type macrophages, and thus reduces the inflammatory response (Figure 12A).…”
Section: Treatment Of Motor Systemmentioning
confidence: 99%
“…(A) H 2 O 2 -driven MnO 2 nanozyme based on the arthritis microenvironment. Adapted under the CC BY license from ref . Copyright 2022 The Authors.…”
Section: Therapeutic Application Of Disease Microenvironment Remodeli...mentioning
confidence: 99%
“…An intriguing strategy involves the creation of MnO 2 -nanomotors for the purpose of active rheumatoid arthritis therapy. [18] While this innovative material shows promise, its reliance on peroxide raises concerns about potential impacts on cell viability. Moreover, the present study has concentrated on the analysis of NM mobility in aqueous surroundings, extending up to 10 mm H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] MNMs are micro-/nanoscale devices capable of converting different forms of energy sources into mechanical force, hence producing autonomous motion to fulfill the designated tasks. [22][23][24][25] The propelling force is expected to endow MNMs with the kinetic motion to overcome the biological barriers, [26] for instance, biofouling, [27] blood-brain barrier, [28] mucosal, [29] and dense extracellular matrix. [30] However, once entering the bloodstream, MNMs may be rapidly identified by mononuclear phagocytes and then eliminated from systemic blood circulation.…”
Section: Introductionmentioning
confidence: 99%